2018
DOI: 10.1039/c8tc01314d
|View full text |Cite
|
Sign up to set email alerts
|

Thermoelectric transport properties of rock-salt SnSe: first-principles investigation

Abstract: Rock-salt SnSe is a new promising thermoelectric material.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
32
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 56 publications
(34 citation statements)
references
References 60 publications
0
32
0
2
Order By: Relevance
“…The trend of the values firstly increases and then decreases with a maximum value at ≈464 K due to the bipolar effect of minority carrier excitation. [17] All the Seebeck coefficients of single-crystal SnSe are lower than those of polycrystalline SnSe at the same measured temperature, which is due to the increased carrier concentration derived from a small energy gap around 0.20 eV and a large electronic density of states in the cubic rock-salt phase. [18] The electrical conductivities of polycrystalline and single-crystal rock-salt SnSe show different temperature-dependent trends (Figure 3b).…”
mentioning
confidence: 89%
See 3 more Smart Citations
“…The trend of the values firstly increases and then decreases with a maximum value at ≈464 K due to the bipolar effect of minority carrier excitation. [17] All the Seebeck coefficients of single-crystal SnSe are lower than those of polycrystalline SnSe at the same measured temperature, which is due to the increased carrier concentration derived from a small energy gap around 0.20 eV and a large electronic density of states in the cubic rock-salt phase. [18] The electrical conductivities of polycrystalline and single-crystal rock-salt SnSe show different temperature-dependent trends (Figure 3b).…”
mentioning
confidence: 89%
“…The thermoelectric property of single-crystal SnSe fiber with rock-salt Fm3 m phase has not been reported so far, even though the theoretical studies on polycrystalline SnSe bulk materials with rock-salt phase have indicated that rock-salt SnSe is a very promising material for high-performance thermoelectrics. [17,18] Here, we experimentally measure the thermoelectric properties along the axial direction as a function of temperature for SnSe fibers with both polycrystalline and single-crystal rock-salt structures. As shown in Figure 3a, both the Seebeck coefficients of polycrystalline and single-crystal SnSe fiber are positive, which means they are p-type semiconductors.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…18,21 Rocksalt SnS can be stabilised under certain conditions such as epitaxial growth, 20,22 whereas rocksalt SnSe is a dynamically stable phase under ambient conditions. 23 We therefore focus on the Pnma, Cmcm, rocksalt and π-cubic phases, the structures of which are illustrated in Figure 1.…”
Section: Introductionmentioning
confidence: 99%